2020
DOI: 10.1080/09584935.2020.1770200
|View full text |Cite
|
Sign up to set email alerts
|

The hydro-social dynamics of exclusion and water insecurity of Dalits in peri-urban Kathmandu Valley, Nepal: fluidyetunchanging

Abstract: Processes of urbanisation create peri-urban spaces that are socially and institutionally fluid. In this article, we analyse how contestations and competition over declining water resources in peri-urban Kathmandu Valley in Nepal reshape water use, access and rights as well as user communities themselves, by creating and reproducing new and existing exclusions and solidarities. Traditional caste-based discriminatory practices, prohibiting Dalits from physically accessing water from sources used by higher castes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Dynamics of the socio-economic landscapes on the basin elucidates the gaps that exist in the water sector despite numerous water sector reforms (Bernauer and Böhmelt, 2020;Okpara et al, 2015;UNESCO, 2018). This finding corroborates with those of (Isaboke, 2015) who posited that over-abstraction of water by large-scale farmers 90% of which is unauthorized among water users are responsible for reduced water volumes in the downstream increasing frequency of conflicts among water users (Shrestha et al, 2020(Shrestha et al, , 2018. Water conflicts between the upstream and downstream users arise from over exploitation with increased abstractions upstream at the expense of the downstream water users (Kiteme, 2020).…”
Section: Resultssupporting
confidence: 87%
“…Dynamics of the socio-economic landscapes on the basin elucidates the gaps that exist in the water sector despite numerous water sector reforms (Bernauer and Böhmelt, 2020;Okpara et al, 2015;UNESCO, 2018). This finding corroborates with those of (Isaboke, 2015) who posited that over-abstraction of water by large-scale farmers 90% of which is unauthorized among water users are responsible for reduced water volumes in the downstream increasing frequency of conflicts among water users (Shrestha et al, 2020(Shrestha et al, , 2018. Water conflicts between the upstream and downstream users arise from over exploitation with increased abstractions upstream at the expense of the downstream water users (Kiteme, 2020).…”
Section: Resultssupporting
confidence: 87%
“…Analysis of data also shows that Dalits are, at times, denied of water access in the public water tap labeling them as untouchables. Such conflicts between Dalits and non-Dalits in which the higher caste people do not allow Dalits to fetch water from public tap are also noted by Pokharel et al (2019) and in Lamatar, an urbanizing region in Kathmandu Valley (Shrestha et al, 2020). Thus, there is an implication that equitable distribution of water to all the residents, both at the core and peripheral regions, need a long-term planning with transformative policy for practice, taking into consideration the socioeconomic related challenges.…”
Section: Discussionmentioning
confidence: 61%
“…As a consequence, public toilets and drinking water sources can become contested spaces in places like rural India and Nepal, where the supply and availability of such goods is scarce to begin with. Elite capture of these goods and services-often by those higher on the social hierarchy-and active exclusion of lower-castes, is commonplace (Shrestha et al, 2020). On the other hand, less access to health services by ethnic minorities can be exacerbated by lack of trust and perceived experiences of abasement at the hand of health care workers (Panday et al, 2019).…”
Section: Social Identity In Nepalmentioning
confidence: 99%
“…Studies have shown that WASH and health‐service improvements have often disproportionately benefitted better‐off populations (McGranahan, 2015; Narayanan et al, 2012) despite having greater potential benefits for poorer people (Bartram & Cairncross, 2010; Rheingans et al, 2014). At the same time, in many countries, factors beyond wealth, such as norms, social structures, and social identities, matter for key well‐being outcomes (Sapkota et al, 2016; Shrestha et al, 2020). To the best of our knowledge, the relationship between access to WASH and health services, and social identity has been less explored than the relationship between access to WASH/health services and wealth.…”
Section: Introductionmentioning
confidence: 99%